Mathematical modelling of carbon dioxide dissolution and reaction processes - Mitchell, Mark J. (2012)
Carbon dioxide dissolution into water is a ubiquitous chemical process on earth, and having a full understanding of this process is becoming ever more important as we seek to understand the consequences of 250 years of exponentially-increasing anthropogenic C02 emissions to the atmosphere since the start of the Industrial Revolution. We examine the dissolution of C02 into water in a number of contexts.